U. S. Department of agriculture, Porto Rico section, climate and crop service, weather bureau - Todd, Roberto H.; Geddings, R. M. (My University, 1899)
Weekly crop bolletin: week ending saturdays, august 26, 1899.
Keywords: Departamento de Agricultura de Estados Unidos; United States. Department of Agriculture.; Meteorology.; Meteorologia.; United States. Weather Bureau.; Moore, Willis L.